Mass spectrometry meets the challenge of understanding the complexity of the lipoproteome: recent findings regarding proteins involved in dyslipidemia and cardiovascular disease. (3rd September 2015) - Singh, Sasha A; Miyosawa, Katsutoshi; Aikawa, Masanori
Abstract : Despite the fact that link between dyslipidemia and atherosclerosis was made over 100 years ago, atherosclerosis remains a major cause of morbidity and mortality worldwide. Major efforts focus towards understanding lipid metabolism, particularly by studying its particle compartments in circulation: the lipoproteins. In recent years, mass spectrometry has played an integral role in the deep sequencing of the lipoproteome and in metabolism studies conducted in vivo. This review highlights the path of lipoprotein research towards state-of-the-art mass spectrometry with special emphasis on the method of selected reaction monitoring and its impact on apolipoprotein metabolism studies. Also presented is what is expected for the lipoprotein field with the recent advent of high resolution/accurate mass parallel reaction monitoring mass spectrometry. The benefits of high resolution/accurate mass measurements are demonstrated by example instrument workflows and by detailing a novel method to quantify very low levels of circulating proprotein convertase subtilisin-kexin type 9 in rabbit. It is anticipated that future clinical studies or clinical trials aimed to treat dyslipidemia by manipulating key regulatory proteins will benefit from the new and exciting opportunities afforded by the latest technologies in mass spectrometry.